Unveiling Employee Fraud in Banking: Understanding the Influential Factors : Membongkar Penipuan Karyawan di Perbankan: Memahami Faktor-faktor yang Mempengaruhi. - Mei Rahmawati; Imelda Dian Rahmawati (Academia Open, 2022)
This quantitative study examines the impact of pressure, opportunity, rationalization, and ability on fraudulent behavior among banking employees. Using a descriptive approach, the research collected data through questionnaires to analyze the development of employee fraud within the banking sector. The results reveal that pressure, rationalization, and ability have a significant partial effect on employee fraud, while opportunity does not exhibit any influence. These findings shed light on the complex dynamics of employee fraud in the banking industry and have implications for improving fraud prevention strategies. Highlights: Understanding employee fraud: This study delves into the complex dynamics and underlying factors that contribute to fraudulent behavior among banking employees. Influential factors: The research examines the impact of pressure, opportunity, rationalization, and ability on employee fraud within the banking sector. Unveiling the truth: By exploring these influential factors, this study aims to shed light on employee fraud and provide insights for developing effective prevention and detection measures in the banking industry. Keywords: Employee fraud, banking, influential factors, understanding, uncovering.